Which are the most frequently involved peripheral joints in calcium pyrophosphate crystal deposition at imaging? A systematic literature review and meta-analysis by the OMERACT ultrasound – CPPD subgroup - Adinolfi, Antonella; Sirotti, Silvia; Sakellariou, Garifallia; Cipolletta, Edoardo; Filippucci, Emilio; Porta, Francesco; Zanetti, Anna; Ughi, Nicola; Sarzi-Puttini, Piercarlo; Scirè, Carlo Alberto; Keen, Helen; Pineda, Carlos; et al. (Frontiers in Medicine, 2023)
Objectives To identify the prevalence of calcium pyrophosphate crystal deposition (CPPD) using ultrasound and conventional radiology at peripheral joints in patients with suspected or definite CPPD. Methods A systematic literature search was performed in PubMed and Embase using pre-defined search strategies from inception to April 2021 to identify studies that evaluated conventional radiology and ultrasound in detecting CPPD at peripheral joints, including definite or suspected CPPD [Research question 1 (RQ1) and Research Question 2 (RQ2), respectively]. For the meta-analysis, the first, second, and third sub-analysis included studies with the knee, and knee or wrist as the index joint for CPPD (without restrictions on the reference standard) and synovial fluid analysis or histology as a reference standard (without restrictions on the index joint), respectively. Results One-thousand eight hundred and twenty-seven manuscripts were identified, of which 94 articles were finally included. Twenty-two and seventy-two papers were included in RQ1 and RQ2, respectively. The knee had the highest prevalence for RQ1 and RQ2 by both conventional radiology and ultrasound, followed by the wrist with the highest prevalence for RQ1. The hand had the lowest CPPD prevalence. The third sub-analysis showed a higher CPPD prevalence on ultrasound than conventional radiology at the knee (only data available). Conclusion Among all peripheral joints, the knees and wrists could be regarded as the target joints for CPPD detection by imaging. Furthermore, ultrasound seems to detect a higher number of calcium pyrophosphate deposits than conventional radiology, even when using a more restrictive reference standard.